Penyidikan Terhadap Anggota Militer Yang Melakukan Tindak Pidana Umum dan Tindak Pidana Korupsi - Jacob Hattu; Astuti Nur Fadillah (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2023)
The Indonesian Constitution states that all citizens have equal status under the law and government and are obliged to uphold the law and government without exception. The law as a commander who does not regard anyone, whether from officials, businessmen, members of the military or ordinary people, has the same rights and position before the law. TNI soldiers are subject to the authority of military justice in cases of violations of military law and are subject to the authority of general justice in cases of violations of general criminal law or corruption law as a special criminal law. This is due to deviations both from a material and formal perspective. Investigations in the military environment are carried out by the Military Police against soldiers who commit non-common crimes.